Representation of Local Wisdom in the Character of Mahar in the Film Laskar Pelangi: The Context of Arts Education - Trisnawati, Eky; Agustin, Kurnia Dwi Marandtika (Universitas Nusantara PGRI Kediri, 2025)
This study analyzes the representation of local wisdom-based art education through the character Mahar in the film Laskar Pelangi (The Rainbow Troops). Mahar, who shows a strong inclination towards art and traditional music, functions as a vital cultural symbol within the Belitung Malay community. The research uses a qualitative descriptive method with an intrinsic approach to explore the implicit cultural representations. Data were gathered via key scene observation, dialogue, and visual elements. Source triangulation and limited member checking ensured data trustworthiness. Findings show that Mahar represents local wisdom primarily through the use of the rebana (traditional frame drum) and the song